Effect of Liquid Organic Applications of Ananas Comosus (L.) Merr. and Citrullus Colocynthys (L.) Schrad. on Soil Fertility in Latosol Soils and Growth and Yield of Vigna Unguiculata Ssp. Sesquipedalis Plants - LUBIS, Erwin Junaidi (Loka: Journal Of Environmental Sciences, 2024)
Purpose:The need for fruit, especially Ananas comosus (L.) Merr. and Citrullus colocynthys (L.) Schrad. Fruit is increasing in the world demand. Ananas comosus (L.) Merr. fruit and Citrullus colocynthys (L.) Schrad. Fruits are very suitable for the health of the human body as a health vitamin enhancer, such as Vitamin C, A, Fibre and Potassium, and their role is very important. However, for health, it is very good for health and soil fertility, because Ananas comosus (L.) Merr. fruit contains 78-87% citric acid, which is found in organic acids other than malic acid and oxalic acid, and the content of Citrullus colocynthys (L.) Schrad. fruit. has a relatively high level of acidity compared to Ananas comosus (L.) Merr. fruit so that it can limit the level of acidity in the effect of citric acid Ananas comosus (L.) Merr. fruit and also good for the growth and yield of Vigna unguiculata ssp. Sesquipedalis.Methodology:This Study used a Factorial Randomized Group Design (RGD). This research was conducted on land located in Pinang Sebatang Timur Village, Tualang District, Siak Regency.Findings:In this study, it was found that the application of mixed formulation of Ananas comosus (L.) Merr. and Citrullus colocynthys (L.) Schrad. fruit as much as 300 ml.polybag-1 mixed with nutrient fertilizer 12.12.17.2 as much as 10 g.polybag-1. Able to increase the growth of Vigna unguiculata ssp. Sesquipedalis plants are well and fertile and have better production results.Implication:In this study, it is indicated to apply it to different soil types as well in order to see the reaction of soil fertility.